Determination of Barriers to E-Commerce in Companies Producing Sports Equipment and Goods: the Perspective of Sport Managers in Iran - Seyed Gholamreza Razavi; Seyed Emad Hosseini; Seyed Mohammad Hossein Razavi (The Society of Aging and Physical Activity (SAPA), 2014)
Today, e-commerce has become a top priority for organizations. By getting use of the Internet, organizations can significantly influence the attitudes of their customers and encourage them to benefit from the services provided by them. Consequently, organizations can affordably become a leader in the market, supply, delivery, and service. Furthermore, development of e-commerce in all existing fields is faced with major obstacles and challenges. Hence, the objective of the present paper was to identify the obstacles to e-commerce in companies producing sports equipment and goods from the perspective of sports managers in Iran. Statistical population included sports general directors of youth and sports offices, presidents of active federations, and executive managers of Ministry of Youth and Sports. Due to limited number of population members, it was completely considered as the sample (n=57). The required data were collected in two parts; firstly, data on theatrical information and previous studies were collected through reviewing the library resources, the Internet, papers, and dissertations about the barriers to e-commerce and second, a questionnaire was used to collect information about the research questions. The results showed that 7 factors including readiness of customers, readiness of companies, administrative barriers, lack of adequate competition, technological barriers, legal barriers, and financial barriers with coefficients of 0.883, 0.859, 0.853, 0.836, 0.801, 0.796, and 0.692, respectively, have the first to seventh ranking among the barriers to e-commerce in this sector.